The Role of Resilience, Self-Efficacy, and Work Stress Management of Nurses Through Emotional Intelligence Training: A Literature Review - Theresia Yeti Resmiati; Catharina Dwiana Wijayanti (Indonesian Journal of Global Health Research, 2025)
Emotional intelligence training can be an effective approach to improve resilience, self-efficacy, and reduce work stress, especially in demanding work environments such as hospitals. This study aims to analyze the effectiveness of emotional intelligence training in improving resilience, self-efficacy, and reducing work stress in nurses. This research is a literature review of various indexed journals from 2020 - 2024 with the keywords, emotional intelligence training, job stress, resilience, self-efficacy, and accessed via Google Scholar, Science Direct, PubMed, ProQuest, and Gale Cengage. Various relevant studies were identified and analyzed to gain an in-depth understanding of the relationship between emotional intelligence training, resilience, self-efficacy, and job stress in nurses. The results of the review indicate that emotional intelligence training has consistently been shown to improve resilience and strengthen self-efficacy, which ultimately reduces work stress. This review provides a theoretical and empirical basis for the development of training programs in the health sector, especially in supporting the mental well-being of medical personnel.